Slopes and intercepts from log-log correlations of gas/particle quotient and octanol-air partition coefficient (vapor-pressure) for semi-volatile organic compounds: II. Theoretical predictions vs. monitoring. (June 2021) - Qiao, Li-Na; Ma, Wan-Li; Zhang, Zi-Feng; Liu, Li-Yan; Song, Wei-Wei; Jia, Hong-Liang; Zhu, Ning-Zheng; Li, Wen-Long; Macdonald, Robie W.; Nikolaev, Anatoly; Li, Yi-Fan
Abstract: The logarithm of gas/particle (G/P) partition quotient (log K P ) has been found to have a linear relationship with log K OA (octanol-air partition coefficient) with slope m o and intercept b o and log P L (subcooled liquid vapor pressure) with slope m p and intercept b p . In the sister paper of the present work, analytical equations to predict the slope m o and intercept b o based on log K OA and predict the slope m p and intercept b p based on log P L are developed using steady state theory. In this work, the equations are evaluated using world-wide monitoring data (262 pairs for m o and b o values and 292 pairs for m p and b p values produced from more than 10, 000 monitiring data worldwide) for selected seven groups of semi-volatile organic compounds (SVOCs), including polybrominated diphenyl ethers (PBDEs), polychlorinated dibenzo-p-dioxins and polychorinated dibenzofurans (PCDD/Fs), polyclorinated biphenyl (PCBs), polycyclic aromatic hydrocarbons (PAHs), polychlorinated naphthalenes (PCNs), organochlorinated pesticides (OCPs), novel brominated flame retardants (NBFRs), and other selected halogenated flame retardants. The slopes and intercepts predicted by the steady state equations reproduce the trends observed in monitoring regression results for the seven SVOC groups, with 44.4% of the variation of monitoring m o values accounted for by log K OA and 48.2% of the variation of monitoring m p values accounted for by log P L . Theoretically, the values of m o can be any value between 0 and 1 dependent on the values of K OA, and are not constrained to 1 as in equilibrium theory. Likewise, the values of m p can be any value between 0 and -1 dependent on the values of P L, and not constrained to −1 predicted by the equilibrium theory. The influence of sampling artifacts on the G/P partitioning of SVOCs has most likely been overemphasized by the equilibrium theory. Thus, the equilibrium approach should be abandoned in favor of the steady state approach for calculating the G/P partition quotients for SVOCs with high K OA values (>10 11.38 ) or low P L values (<10 −4.92 ). Highlights: Slopes and intercepts of SOVCs are predicted based on steady state equations. The prediction results compare well with the monitoring data worldwide. Parameters K OA and P L are the major factors to determine the deviation of m and b . The slopes can characterize the equilibrium and non-equilibrium statuses of SVOCs in air.